Rogue heroes : the history of the SAS, Britain's secret special forces unit that sabotaged the Nazis and changed the nature of the war - Macintyre, Ben, 1963- (Crown, 2016)
Britain's Special Air Service--or SAS--was the brainchild of David Stirling, a young, gadabout aristocrat with a remarkable strategic mind. Where his colleagues looked at a map of World War II's African theater and saw a protracted struggle with Rommel's desert forces, Stirling saw an opportunity: given a small number of elite, well-trained men, he could parachute behind Nazi lines and sabotage their airplanes and supplies. Paired with his constitutional opposite, the disciplined martinet Jock Lewes, Stirling assembled a revolutionary fighting force that would upend not just the balance of the war, but the nature of combat itself. He faced no little resistance from those who found his tactics ungentlemanly or beyond the pale, but in the SAS's remarkable exploits facing the Nazis in the Africa and then on the Continent can be found the seeds of nearly all special forces units that would follow. Bringing his keen eye for psychological detail to a riveting wartime narrative, Ben Macintyre uses his unprecedented access to SAS archives to shine a light inside a legendary unit long shrouded in secrecy. The result is not just a tremendous war story, but a fascinating group portrait of men of whom history and country asked the most.--Adapted from dust jacket and publisher description.